Genre et horaires de travail : un nouveau regard à partir de la théorie de la segmentation - Anne Bustreel; Martine Pernod-Lemattre (Revue de la Régulation)
The present paper investigates how employer working time policies are related to the gender composition of the labour force. To study theses policies, we opted for a qualitative survey, based on semi-structured interviews of HR offciers. It proposes a gendered reinterpretation of time systems, as described and analysed in the labour force segmentation perspective: the results-based time system, the fragmented time system, the standard time system. The findings indicate that gender has an ambiguous influence on working time arrangements: depending on contexts, it may improve or worsen working conditions.